Overview Of Malaria Diagnosis Methods In Bitung City Community Health Center - Monalisa, Monalisa; Victor D. Pijoh; Greta J. P. Wahongan (Jurnal EduHealth, 2025)
Malaria remains one of the leading causes of morbidity and mortality in many countries. A definitive diagnosis of malaria can be made through microscopic examination or Rapid Diagnostic Tests (RDTs). Both microscopic examination and RDT have their own characteristics, advantages, and limitations. This study aims to describe the methods of malaria diagnosis at community health centers in Bitung City. A descriptive research design with a cross-sectional approach was used in this study. Data were obtained through interviews with nine health workers, including laboratory assistants and malaria program coordinators, from nine community health centers in Bitung City. The results showed that microscopic examination was available in only five community health centers. These centers confirmed RDT results and identified Plasmodium species through microscopic examination. In the primary health centers where only RDT was available, three referred patients to more equipped facilities, and one made a diagnosis using only RDT. The conclusion of this study is that RDT is available in all community health centers, whereas microscopic examination is available in only five community health centers due to limited diagnostic tools and human resources.